2010
DOI: 10.1177/1356766709357486
|View full text |Cite
|
Sign up to set email alerts
|

Segmenting special interest visitors to a destination region based on the volume of their expenditures: an application to rail-trail users

Abstract: Various general tourist markets have been successfully segmented based on the volume of tourists' expenditures in destination areas. However, the approach has been rarely employed in more narrowly defined 'special interest' tourist markets. This study tested the viability of expenditure-based segmentation in the case of a special interest market comprised of visitors to a rail-trail in the Black Hills of South Dakota, USA. Nonresident visitors were classified as light, medium, and heavy spenders based on their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
(28 reference statements)
1
7
0
Order By: Relevance
“…The survey was conducted in response to a request by the MTC for information to guide the product development, target marketing, and advertising purchase decisions necessary to increase aggregate visitor spending along the Trail. These marketing-oriented results are reported in Spencer (2010). Additional results on the characteristics and behaviour patterns of local versus tourist visitors are reported in Spencer (2012).…”
Section: Study Regionsupporting
confidence: 55%
“…The survey was conducted in response to a request by the MTC for information to guide the product development, target marketing, and advertising purchase decisions necessary to increase aggregate visitor spending along the Trail. These marketing-oriented results are reported in Spencer (2010). Additional results on the characteristics and behaviour patterns of local versus tourist visitors are reported in Spencer (2012).…”
Section: Study Regionsupporting
confidence: 55%
“…Despite the length of time since the early studies were published, Pizam and Reichel (1979) and Spotts and Mahoney (1991), along with Mok and Iverson (2000), continue to be regarded not only as pioneers in this area but as the point from which current studies begin. Spencer (2010), for example, specifically states that his methodology follows that of Mok and Iverson. This is notwithstanding the fact that the early papers were primarily concerned with exploring only the viability of using market segmentation in the tourism context.…”
Section: Chronological Overview Of Current Studiesmentioning
confidence: 99%
“…Higher engagement with the destination's offerings or engagement with a specific activity appears to be the one common factor associated with high expenditure in all six studies. Spotts and Mahoney (1991) and Spencer (2010) note their high spenders are engaged in a range of activities. In other cases, the high-spending segment is involved in a specific activity, such as fishing and visiting open spaces (Wilton and Nickerson, 2006), challenging activities (Mehmetoglu, 2007), downhill skiing (Fredman, 2008) and mountain biking (Spencer).…”
Section: The Tourism Market Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies examining various special-interest tourism segments (e.g., rail-trail, fishing), of which wine tourism is one, have demonstrated that the number of activities participated in while visiting a region informs the tourist's experience (Oh & Schuett, 2010;Spencer, 2010).…”
Section: Mediating Effect Of the 4es On Behavioral Intentionsmentioning
confidence: 99%